GOVERNMENT COMMUNICATION PATTERNS IN THE DISASTER RESILIENT VILLAGE PROGRAM AS AN EFFORT TO DEAL WITH COVID-19 - R. Hendhrasukma Juniar (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2022)
Kampung Tangguh is a generic concept that has three main components, namely the theoretical basis, the level of movement, and the pattern of movement. Communication is expected to function as a means, so that the community responds to behavior that is reasonably done in eliminating or reducing risk. The importance of good government communication patterns is increasingly needed during the COVID-19 pandemic given the increasing development of the pandemic. This study aims to determine the pattern of government communication in the Kampung Tangguh program as an effort to handle the COVID-19 pandemic in East Java. This research uses qualitative research with descriptive method. Data collection procedures used are interviews, observation and documentation. The informants in this study were the COVID-19 task force team, the head of the Neighborhood Association and the head of the Citizens Association. Technique of data validity using triangulation test. The data analysis technique uses descriptive qualitative analysis with three flows, namely data condensation, data display and drawing conclusions. The results in this study indicate that the government's communication pattern in the Kampung Tangguh program as an effort to handle the COVID-19 pandemic in East Java has been going well and in stages, where there is more interpersonal communication between the government and the task force team and the task force team to the community.